THE ANALYSIS OF IMPLICATURESUSED IN ENGLISH SLOGANSOF MEDICINE ADVERTISEMENT - Sri Widodo (p-ISSN 2356-0576, 2020)
Abstract: This research is a descriptive qualitativeresearch which concerns withthe analysis of implicatures used in English slogans of medicine advertisement. Mostly English slogans in medicine advertisement employ implicature, and people should use their knowledge to draw the implicit meaning of the slogans.Here, the researcher used documentation as the method in collectingdata.Thedataweredownloadedfromtheinternetand analyzed usingimplicature theory.From the datawhichhadbeenanalyzed,there are25dataemploy implicature found. 2 data (8%) of English slogans used in medicine advertisement belong to generalized conversational implicature, 13 data (52%) belong to particularized conversational implicature, and 10 data (40%) belong to conventional implicature. The researchers suggest other researchers to conduct any other research that deals with implicature analysis and to make their research being able to be applied in English language teaching. Therefore, the result oftheir study will be more useful.Keywords: implicature, slogan, medicine advertisement.